2018
DOI: 10.1093/scan/nsy042
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac interoceptive learning is modulated by emotional valence perceived from facial expressions

Abstract: Interoception refers to the processing of homeostatic bodily signals. Research demonstrates that interoceptive markers can be modulated via exteroceptive stimuli and suggests that the emotional content of this information may produce distinct interoceptive outcomes. Here, we explored the impact of differently valenced exteroceptive information on the processing of interoceptive signals. Participants completed a repetition-suppression paradigm viewing repeating or alternating faces. In experiment 1, faces wore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 47 publications
6
29
1
Order By: Relevance
“…In the current study, affective repetition effects on cardiac interoceptive processing were only observed in repetition blocks, suggesting that the repetition effects were highly dependent on probability context. Our results are in line with previous evidence that highlight the role of expectations in repetition effects (Marshall et al, 2017;Marshall et al, 2018) supporting the idea that repetition suppression is a surprise-context-dependent phenomenon that occurs via probability context. The evidence that affective repetition effects were only present when the likelihood of repetitions was high suggests that the HEP modulation may result from global top-down modulation based on probability context (i.e., highrepetition probability) rather than from lower level sources of local prediction signals from the preceding trial.…”
Section: Context-dependent Affective Prediction Effects On Cardiac supporting
confidence: 92%
See 3 more Smart Citations
“…In the current study, affective repetition effects on cardiac interoceptive processing were only observed in repetition blocks, suggesting that the repetition effects were highly dependent on probability context. Our results are in line with previous evidence that highlight the role of expectations in repetition effects (Marshall et al, 2017;Marshall et al, 2018) supporting the idea that repetition suppression is a surprise-context-dependent phenomenon that occurs via probability context. The evidence that affective repetition effects were only present when the likelihood of repetitions was high suggests that the HEP modulation may result from global top-down modulation based on probability context (i.e., highrepetition probability) rather than from lower level sources of local prediction signals from the preceding trial.…”
Section: Context-dependent Affective Prediction Effects On Cardiac supporting
confidence: 92%
“…These results contrast with previous ERP studies reporting repetition suppression effects on early VEPs (e.g., Engell & McCarthy, 2014;Nemrodov et al, 2015;Vizioli et al, 2010). A recently published ERP study has shown that repetition of the same facial identity posing a negative expression leads to repetition suppression of both VEPs and HEP, in comparison to when posing a neutral expression (Marshall et al, 2017, see also Marshall et al, 2018). By contrast, in our paradigm the repetition manipulation was made in regards to the affective content of the facial expression, that is, emotion component, as opposed to the identity component.…”
Section: Affective Inference Does Not Impact Visual Cortical Responsescontrasting
confidence: 79%
See 2 more Smart Citations
“…HERs vary with emotions while viewing mood-inducing video clips [122] or while judging the emotional expression of faces [123]. Based on the hypothesis that specific emotions might lead to precise interoceptive predictions [11], the expected repetition of an emotional facial expression leads to a reduction (for angry faces) or increase (for sad or pain faces) in HER amplitude [124,125]. Because emotions are accompanied by changes in bodily parameters, with a linear relationship between heart rate and valence, and between skin conductance and arousal [126], the emotion-related modulations of HERs might reflect either neural responses to changes in bodily state or the cortical mechanisms driving bodily changes [127].…”
Section: Heartbeat Evoked Responses and Emotionsmentioning
confidence: 99%